PENGARUH MOTIVASI FUNGSIONAL TERHADAP MINAT MAHASISWA MENJADI VOLUNTEER PENDIDIKAN DI SOLO MENGAJAR - Ervin Devi Pratiwi; Sunarto Sunarto; Muhammad Sabandi (Department of Economics Education, Universitas Sebelas Maret, 2018)
The aim of this research is to find out the influencing factors of the students’ interest to be a volunteers in education field at Solo Mengajar. Besides, this research is also aimed to find out the difference between functional motivation of men and women. This research belongs to quantitative research with sample survey as the method to conduct the research. The sampling methods used in this research are proportionate random sampling and simple random sampling with lottery. The data analysis technique is Partial Least Square (PLS). Based on the results of this study concluded that the functional motivation positive and significant effect on the interests of students to volunteer education in Solo Mengajar. Conclusions further explain the moderating effects of gender. The results of the t-statistic analysis showed that gender had a significant result on understanding motivation and protective.